Computational investigation of Y. aloifolia variegate as anti-Human Immunodeficiency Virus (HIV) targeting HIV-1 protease: A multiscale in-silico exploration - Riyan Alifbi Putera Irsal; Gusnia Meilin Gholam; Maheswari Alfira Dwicesaria; Fernanda Chairunisa (Elsevier, 2024)
Introduction: Human Immunodeficiency Virus (HIV) is a global challenge for the health sector due to the absence of a definitive cure. More than 38 million people are affected by the disease worldwide, with approximately 1.5 million new cases reported annually. This situation has spurred continued efforts in searching for drug candidates. Meanwhile, rutin, luteolin, and quercetin are compounds known for efficacy in treating infectious diseases. The compounds have also been detected in Yucca aloifolia (絲蘭) variegate L. Therefore, this study aimed to conduct a computational investigation utilizing multiscale in silico exploration to assess the potential of Y. aloifolia as an anti-HIV agent targeting HIV-1 Protease (H1P). Methods: For the in silico study, the three-dimensional structure of H1P (PDB: 5V4Y) was retrieved and prepared using YASARA Structure. The binding pockets were identified using Cavity Plus server, and ligands were obtained from Y. aloifolia leaves alcohol extract. Furthermore, molecular docking was conducted with YASARA Structure to predict binding energies, followed by QSAR analysis for activity prediction. Density Functional Theory (DFT) analysis was performed to assess stability and reactivity, while toxicity was evaluated using ProTox 3.0. Molecular dynamics (MD) simulation and Molecular Mechanics Poisson-Boltzmann Surface Area (MM-PBSA) calculation were also conducted for further analysis. Results: The results showed that Ramachandran plot analysis indicated favorable residue distribution based on the evaluation of enzyme preparation quality. Cavity Plus identified potential binding sites, with cavity no.2 showing the highest druggability. Molecular docking showed rutin and isorhamnetin-3-O-rutinoside as top binders to H1P, with favorable binding energies. Moreover, post-docking analysis produced specific interactions between ligands and the receptor. PASS prediction indicated the potential of rutin and isorhamnetin-3-O-rutinoside (narcissin) as H1P inhibitors. DFT analysis assessed stability, showing comparable values for the investigated compounds. Toxicity analysis suggested both compounds to be non-toxic. Finally, MD simulation demonstrated the superior stability and binding affinity of rutin compared to isorhamnetin-3-O-rutinoside and the control drug, grl-09510. Discussion: Rutin, hecogenin, and isorhamnetin-3-O-rutinoside from Y. aloifolia (絲蘭) leaves showed potential as H1P inhibitors through in silico study. Docking simulations indicated that rutin had the most favorable binding interactions, while MD simulation showed only the rutin-H1P complex to be stable, signifying the potential for further drug development. Rutin was identified as a promising lead for H1P inhibition due to its strong binding, stability, and predicted safety properties, underscoring the need for wet lab validation.